Radiofrequency and optical satellite link budgeting calculator - Rosas-Palacios, A.; Casillas-Aviña, G. E.; Yáñez-Casas, G. A.; López-Balcázar, C. A.; Hernández-Gómez, J. J. (Journal of physics. Conference series, 2024)
Satellite communications represent one of the most widely used communication systems nowadays. From the 50’s of 20th century up to the present, the demand for satellite services has increased rapidly, so the need to design and implement reliable, up-to-date systems that meet the needs of users is increasingly imperative. Technological progress also implies a better use of the radio spectrum and the incorporation of benefits in terms of transmission performance. Traditionally, satellite systems have been implemented in the range corresponding to radio frequency, and more recently, special attention has been paid to the exploration of the spectrum corresponding to optical communications, due to the superior benefits that it offers, despite the set of challenges that its implementation represents. Such advances demand the greatest certainty of operation even from the conception and design stage of the transmission system, since satellite communications are not prone to constant changes and maintenance. The calculation process known as link budget is a tool present in the design of any wireless communications system, and its results determine the efficiency and reliability of the design. However, due to the large number of manufacturers and operators, as well as considering the novelty of using high-performance optical systems, it is difficult to stick to a single method or even to point out one as totally reliable and simple to use. With the purpose of expediting the calculation of link budgets, there are various computational tools that allow this process to be carried out. However, these tools carry the problem of poor compatibility, differences and a low degree of reliability and ease of use. In the present work, the construction and use of a web application is proposed that includes the link budget calculation process for both radio and optical satellite systems, flexible, simple, user-friendly, compatible, and mainly, abode to standardised and documented models for provide reliability and accuracy.